2016
DOI: 10.1088/0029-5515/56/3/036002
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic plasma rotation and Reynolds stress at the plasma edge in the HSX stellarator

Abstract: Using multi-tipped Langmuir probes in the edge of the HSX stellarator, the radial electric field and parallel flows are found to deviate from the values calculated by the neoclassical transport code PENTA for the optimized quasi-helically symmetric (QHS) configuration. To understand whether Reynolds stress might explain the discrepancy, fluctuating floating potential measurements are made at two locations in the torus corresponding to the low field and high field sides of the device. The measurements at the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…It is found that the local Reynolds stress and the resulting zonal flow drive are concentrated on the outboard side, where the normal curvature is negative. These measurements go beyond previously published results [16,17] and motivate complementary turbulence simulations in 3D geometry in order to quantitatively address the magnetic field dependence of microscopic (drift-wave turbulence) and macroscopic (zonal flow) dynamics. This paper is organised as follows.…”
Section: Introductionsupporting
confidence: 58%
“…It is found that the local Reynolds stress and the resulting zonal flow drive are concentrated on the outboard side, where the normal curvature is negative. These measurements go beyond previously published results [16,17] and motivate complementary turbulence simulations in 3D geometry in order to quantitatively address the magnetic field dependence of microscopic (drift-wave turbulence) and macroscopic (zonal flow) dynamics. This paper is organised as follows.…”
Section: Introductionsupporting
confidence: 58%
“…To point this out explicitly, it is possible to both over and underestimate the flux-surface average Reynolds stress by taking a local measurement only. The Reynolds stress have been experimentally found to have the opposite sign at two different poloidal locations [38]. From the present study it can be concluded that a better understanding of the spatial distribution of the Reynolds stress is necessary for a proper interpretation of local measurements involving simulations with realistic field geometry.…”
Section: Discussionmentioning
confidence: 53%
“…Estimates indicate that if the neutral friction were lowered, turbulent Reynolds stress could also be more significant than neoclassical viscosity in QHS [8]. Previous probe measurements of Reynolds stress suggested that the Reynolds stress could drive significant flow in the edge of HSX, though the result was not conclusive because only two measurements of Reynolds stress were made on a flux surface [32].…”
Section: Discussionmentioning
confidence: 99%